USE OF COLORS FOR HEALTH IMPROVEMENT AND DISEASE PREVENTION POWER: स्वास्थ्य सुधार के लिए रंगों की उपयोगिता एवं रोग निवारण शक्ति - Acharya, Pankaja (International Journal of Research -GRANTHAALAYAH, 2014)
Colors have a definite effect on the human body and mind. Dyed clothes, the color found in the houses, they leave their impact. Whether the sun rays are taken on the body through glass or by placing a colored glass bottle in the sun for six hours after that water is drunk after two hours, its effect also helps in providing healing according to the color. Researchers say that the effect of colors on specific parts of the brain is special, and then the same kind of inspiration goes on for the whole body. Magnetic powers are modulated and change their effect. The effect of colors has been seen directly on the pituitary and pineal glands of the brain. The hypothalamus region has been shown to be agitated and relaxed on this basis. This is why they are helpful in preventing debility and illness. मनुष्य के शरीर और मन पर रंगों का सुनिश्चित प्रभाव पड़ता है। रंगे कपड़े, पुते मकान में जो रंग मिला होता है, वे अपना प्रभाव छोड़ते हैं। काँच के माध्यम से सूर्य किरणों को शरीर पर लिया जाए या रंगीन काँच की बोतल को धूप में छः घण्टे रखकर उस पानी को दो-दो घण्टे बाद पिया जाए तो उसका प्रभाव भी रंग के अनुसार आरोग्य प्रदान करने में काम आता है। शोधकर्ताओं का कथन है कि रंगों का प्रभाव मस्तिष्क के महत्वपूर्ण भागों पर विषेष रूप से पड़ता है और फिर वहाँ से उसी प्रकार प्रेरणा सारे षरीर के लिए चल पड़ती है।अंतःस्त्रावी ग्रन्थियों से स्त्रावित होने वाले हार्मोन इन रंगों के प्रभाव से अपनी क्षमता में रंगों की चुम्बकीय षक्ति से न्यूनाधिक होते है और अपने प्रभाव में परिवर्तन करते हैं। मस्तिष्क की पिट्युटरी और पीनियल ग्रन्थियों पर रंगों का प्रभाव प्रत्यक्ष देखा गया है। हाइपोथैलेमस क्षेत्र को इसी आधार पर उत्तेजित और शांत होते देखा गया है। यही कारण है तो दुर्बलता और रूग्णता का निवारण करने में सहायक होते हैं।